Assortative marriages by body mass index have increased simultaneously with the obesity epidemic - Ajslev, Teresa A.; Ängquist, Lars; Silventoinen, Karri; Gamborg, Michael; Allison, David B.; Baker, Jennifer L.; Sørensen, Thorkild I. (Frontiers in Genetics, 2012)
Background: The genetic predisposition to obesity may have contributed to the obesity epidemic through assortative mating. We investigated whether spouses were positively assorted by body mass index (BMI; =kg/m2) in late childhood, and whether changes in assorted marriage by upper BMI-percentiles occurred during the obesity epidemic. Methods: In the Copenhagen School Health Records Register boys and girls with measures of BMI at age 13 years later became 37 792 spousal-pairs who married from 1945–2010. Trends in the spousal BMI correlations using sex-, age- and birth cohort-specific BMI z-scores across time were investigated. Odds ratios (ORs) of marriage among spouses both with BMI z-scores >90th or >95th percentile compared with marriage among spouses ≤90th percentile were analysed for marriages entered during the years prior to (1945–1970), and during the obesity epidemic (1971–2010). Findings: Spousal BMI correlations were small and stayed similar across time. ORs of marriage among spouses with BMIs >90th percentile at age 13 were 1.21, 1.05–1.39, in 1945–1970, and increased to 1.63, 1.40–1.91, in 1971–2010 (p=0.006). ORs of marriage among spouses both >95th BMI percentile were higher and increased more; from 1.39, 1.10–1.81, to 2.39, 1.85–3.09 (p=0.004). Interpretation: Spousal correlations by pre-marital BMIs were stable during the past 65 years. Yet, assorted marriages between spouses with BMIs in the upper percentiles were observed and increased significantly across the two marriage periods, and this may possibly influence the following generations’ susceptibility to obesity.